2011
DOI: 10.1002/hbm.21416
|View full text |Cite
|
Sign up to set email alerts
|

Localization of pain‐related brain activation: A meta‐analysis of neuroimaging data

Abstract: A meta-analysis of 140 neuroimaging studies was performed using the activation-likelihood-estimate (ALE) method to explore the location and extent of activation in the brain in response to noxious stimuli in healthy volunteers. The first analysis involved the creation of a likelihood map illustrating brain activation common across studies using noxious stimuli. The left thalamus, right anterior cingulate cortex (ACC), bilateral anterior insulae, and left dorsal posterior insula had the highest likelihood of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
259
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(295 citation statements)
references
References 227 publications
(209 reference statements)
35
259
1
Order By: Relevance
“…The finding of significant activity changes solely in this area confirms cumulating evidence from other human reports which demonstrated that it is the most consistently activated area during acute pain perception (Duerden and Albanese, 2013;Garcia-Larrea, 2012;Oertel et al, 2012). In support of this observation, the posterior insula and adjoining medial parietal operculum are the only areas where direct electrical cortical stimulation triggered somatic pain in patients undergoing brain surgery (Mazzola et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…The finding of significant activity changes solely in this area confirms cumulating evidence from other human reports which demonstrated that it is the most consistently activated area during acute pain perception (Duerden and Albanese, 2013;Garcia-Larrea, 2012;Oertel et al, 2012). In support of this observation, the posterior insula and adjoining medial parietal operculum are the only areas where direct electrical cortical stimulation triggered somatic pain in patients undergoing brain surgery (Mazzola et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…In addition to our present finding of stronger right TPJ than left TPJ functional connectivity with the salience network, our seed-based analysis revealed stronger coupling between right TPJ than left TPJ with regions that are well-known to be involved in the sensory-discriminative and affective-motivational aspects of pain (right aINS, SII) (Apkarian et al 2005;Duerden and Albanese 2011). Notably, when we did not apply a cluster significance threshold for the right TPJ Ͼ left TPJ functional connectivity contrast at the level of Z Ͼ 2.3, the aINS and SII findings were bilateral and there was an additional cluster in the MCC (data not shown).…”
Section: Discussionsupporting
confidence: 70%
“…We have previously found that activity in right-lateralized regions within the salience/ ventral attention network, including the right TPJ, encodes the prolonged salience of pain (Downar et al 2003). There is also a high degree of overlap between regions within the salience network and regions that are activated during pain , and a recent meta-analysis suggests that there is a right hemisphere dominance in insula and cingulate cortex activations during painful stimulation (Duerden and Albanese 2011).…”
Section: Discussionmentioning
confidence: 98%
“…The Talairach coordinates of our STG ROIs lie close to the secondary somatosensory area (SII), located at the upper bank of the Lateral Sulcus 26 . In order to exclude possible contamination of our STG ROI by voxels from SII, we conducted a control experiment (similar design as the main experiment using melodies) in which our subjects also performed a visual-motor task during which they typed 7-digit numbers with their right ('3-4-1-3-4-5-1') or left ('1-5-4-3-1-4-3') hands by pressing the digital piano keys and receiving visual feedback of the typed numbers (1 corresponding to the thumb and 5 to the little finger).…”
mentioning
confidence: 99%